Development of University Students’ Motivation with the Help of E-learning - Nickolay V. Kotryakhov; Alfiya R. Masalimova; Zhanna M. Sizova; Rashad A. Kurbanov (Elementary Education Online, 2023)
The urgency of the study is caused by the thrust of contemporary education models to develop a competitive creative personality having the need for continuous self-improvement and self-development. It is possible owing to the high level of students’ learning motivation and accordingly, the motivation to acquire a future profession. It should be emphasized that e-learning technologies have considerable potential in terms of intensification and effectiveness of the system of education. This fact is very important in the context of the educational paradigm of lifelong learning (learning throughout life) within which blended-learning is widely used which assumes an optimum combination of face-to-face and distant (remote) form of interaction between teachers and students. This article is aimed at unlocking (defining) didactic potential of the means of e-learning to enhance motivation of technical specialties students to master the natural-sciences and mathematical disciplines and acquire a profession. The leading method of the study was activity-based approach which enabled us to analyze the problem from the standpoint of dialogue, subjectivity and individuality. In the process of the experimental work, methodologies and techniques were used that allowed to determine with a sufficient degree of reliability the level of students’ motivation for e-learning, and later for professional training. Also, observation, interview, survey techniques were used. The article analyzes theoretical aspects of the use of e-learning to motivate university students to acquire natural science knowledge with the subsequent study of vocational disciplines. On the one hand, the article is a methodological basis for the engineering and technical personnel training system; on the other hand, it reveals some methodical issues dealing with the use of modern means of e-learning to increase the level of learning motivation in general. The article also presents the outcomes of a series of lessons aimed at developing students’ motivation by means of elearning. The materials of the article may be helpful to those who teach at higher education institutions.